Real world experience of response to pirfenidone in patients with idiopathic pulmonary fibrosis: a two centre retrospective study - Eaden, James; Barber, Christopher M.; Renshaw, Stephen; Chaudhuri, Nazia; Bianchi, Stephen (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2020)
Introduction: Pirfenidone has been shown to reduce the decline in forced vital capacity (FVC) compared to placebo in patients with idiopathic pulmonary fibrosis (IPF). Previous studies have suggested that patients with a more rapid decline in FVC during the period before starting pirfenidone experience the greatest benefit from treatment. The purpose of this retrospective observational study was to investigate the response to pirfenidone in IPF patients, comparing two groups stratified by the annual rate of decline in FVC % predicted prior to treatment. Methods: Using the rate of decline in FVC % predicted in the 12 months prior to pirfenidone, patients were stratified into slow (